2020
DOI: 10.1073/pnas.2010303117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of systemic genomic instability in budding yeast

Abstract: Conventional models of genome evolution are centered around the principle that mutations form independently of each other and build up slowly over time. We characterized the occurrence of bursts of genome-wide loss-of-heterozygosity (LOH) in Saccharomyces cerevisiae, providing support for an additional nonindependent and faster mode of mutation accumulation. We initially characterized a yeast clone isolated for carrying an LOH event at a specific chromosome site, and surprisingly found that it also carried mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Acquisition of this extrachromosomal sequence by S. cerevisiae is posited to have occurred through a horizontal gene transfer event, and numerous distinct insertions of this sequence have been identified in the genomes of other strains, primarily in those isolated from wine-making environments 23 . The specific insertion of the Z. bailii circle at this locus on Chr6 appears to be shared by other wild isolates of S. cerevisiae, as we recently identified an identical insertion in one of the Chr6 homologs in the diploid genome of the industrial strain JAY270 24 .…”
Section: Structural Features Of the Yjm311-3 Genomementioning
confidence: 88%
“…Acquisition of this extrachromosomal sequence by S. cerevisiae is posited to have occurred through a horizontal gene transfer event, and numerous distinct insertions of this sequence have been identified in the genomes of other strains, primarily in those isolated from wine-making environments 23 . The specific insertion of the Z. bailii circle at this locus on Chr6 appears to be shared by other wild isolates of S. cerevisiae, as we recently identified an identical insertion in one of the Chr6 homologs in the diploid genome of the industrial strain JAY270 24 .…”
Section: Structural Features Of the Yjm311-3 Genomementioning
confidence: 88%
“…The potential impacts of aneuploidy-driven phenotype switching on population diversity are further heightened when framed within the emergent concept of systemic genomic instability (SGI) 23,24,43,44 . Recent work from our group demonstrated that aneuploidization events often impart systemic genomic changes, with the potential to impact the transmission of many, if not all, chromosomes in the cell concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Most information about the rates of these events was based on the genetic assay system involving single genes or partial chromosomes [ 51 , 52 ]. More recently, subculturing of yeast strains over many generations for mutation accumulation (MA) followed by whole-genome sequencing has allowed a more global analysis of chromosomal rearrangements [ 53 , 54 , 55 , 56 ]. Sui et al [ 53 ] performed MA experiments in a diploid S. cerevisiae strain ( spo11/spo11 ; unable to enter meiosis), identifying chromosomal rearrangements throughout the genome by deep-coverage genome sequencing.…”
Section: Spontaneous and Genotoxic Factor-induced Chromosomal Rearmentioning
confidence: 99%
“…Most strikingly, this work demonstrated that spontaneous chromosomal rearrangements generally involve homologous recombination between non-allelic dispersed repeats in the yeast genome. In a recent study by Sampaio et al [ 55 ], the authors showed that two LOH events coincided at two different chromosomes at rates 14- to 150-fold higher than predicted if these two events originated independently of each other. This finding suggested that multiple genomic alterations can occur simultaneously during a limited time window, possibly as short as a single cycle of cell division [ 55 ].…”
Section: Spontaneous and Genotoxic Factor-induced Chromosomal Rearmentioning
confidence: 99%
See 1 more Smart Citation